2002
DOI: 10.1002/hep.1840360609
|View full text |Cite
|
Sign up to set email alerts
|

NAFLD may be a common underlying liver disease in patients with hepatocellular Carcinoma in the United States

Abstract: The incidence of hepatocellular carcinoma (HCC) in the United States is increasing, but the clinical characteristics of American patients with HCC have not been well described. The aims of this study were to determine the etiology of liver disease and short-term outcome among HCC patients presenting to a single center in the United States. One hundred five consecutive patients with HCC were studied; mean age was 59 years, 67% were men, and 76% were non-Hispanic white. The most common etiology of liver disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
245
3
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(266 citation statements)
references
References 25 publications
(3 reference statements)
13
245
3
5
Order By: Relevance
“…These findings support the hypothesis that NASH is a risk factor for HCC and that it may explain a considerable proportion of cryptogenic HCC cases. In these studies, however, the prevalence of cryptogenic HCC was 7% (Bugianesi et al, 2002) and 9% (Regimbeau et al, 2004), much lower than the 29% reported in a USA study with a high prevalence of obesity and obesity-related metabolic disorders (Marrero et al, 2002).…”
Section: Non-alcoholic Steatohepatitis and Hepatocellular Carcinomamentioning
confidence: 58%
“…These findings support the hypothesis that NASH is a risk factor for HCC and that it may explain a considerable proportion of cryptogenic HCC cases. In these studies, however, the prevalence of cryptogenic HCC was 7% (Bugianesi et al, 2002) and 9% (Regimbeau et al, 2004), much lower than the 29% reported in a USA study with a high prevalence of obesity and obesity-related metabolic disorders (Marrero et al, 2002).…”
Section: Non-alcoholic Steatohepatitis and Hepatocellular Carcinomamentioning
confidence: 58%
“…Similarly, the rate for blacks, starting at 2.5 between 1976 and 1978, reached 5.0 for the period of 2000-2002. Finally, the rate among other racial groups (predominantly Asians) started at 6.0 between 1976 and 1978 and subsequently rose but appeared to have reached a (Marrero et al, 2002) (Table 7). HCV was the underlying cause for the liver disease in 51 percent (39 percent had only HCV as a risk factor and another 12 percent also had a history of chronic alcoholism), 29 percent had cryptogenic liver disease, 10 percent had only heavy alcoholism as a potential etiology, 6 percent were infected with HBV and 4 percent were associated with other conditions.…”
Section: Surveys To Determine the Incidence And Etiology Of Hepatocelmentioning
confidence: 99%
“…That HCC was among the most common of cancers worldwide could then be accounted for by the fact that HBV infection, the leading cause for HCC, is endemic in southeast Asia (Beasley et al, 1981), the most populous area in the world, as well as in sub-Saharan Africa. More recently, it has become apparent that obesity, with its accompanying problems of diabetes mellitus and nonalcoholic steatohepatitis (NASH), represents a growing addition to the causes of HCC (Marrero et al, 2002;Caldwell et al, 2004;El-Serag et al, 2004). Furthermore, evidence is accumulating that both diabetes and chronic alcoholism behave synergistically with HBV and HCV infections in the induction of HCC (Hassan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…51 Cirrhosis resulting from NAFLD accounts for approximately 13% of all cases of hepatocellular carcinoma. 52 Unrelated to the risk of progressive liver disease in NAFLD, fatty liver can accelerate the progression of other forms of chronic liver disease, in particular hepatitis C. 53,54 Pathogenesis of fatty liver…”
Section: Hypertension Metabolic Syndrome and Fatty Livermentioning
confidence: 99%